Hegemony in Digital News: A CDA Approach to Power Relations in Indonesian Social Media - Parthama, I Gusti Ngurah; Qomariana, Yana (International Research and Development for Human Beings (IRDH), 2025)
This study investigates language that constructs and legitimizes power relations in news discourse published on social media platforms during the covid-19 pandemic. Drawing on Fairclough’s (1995) critical discourse analysis framework, the research aims to reveal the ideological mechanisms embedded in linguistic choices used by state actors in shaping public perception. The study employs a qualitative method with data collected through documentation of news texts posted on Facebook. The news test was particularly concerning to government responses on the pandemic. The analysis involves textual examination, intertextuality mapping, and social semiotic interpretation. The findings reveal that government-affiliated discourse employs declarative structures, institutional deixis, and culturally embedded phrases such as gotong royong. It is to promote national unity, responsibility, and trust in leadership. The texts construct an authoritative narrative that normalizes state intervention and discourages dissent through moral appeals and symbolic alignment with cultural norms. Linguistic features are strategically used to legitimize top-down communication and to frame the state as both protector and moral guide. The study concludes that language in social media news discourse serves as an instrument of symbolic power that maintains ideological hegemony under the appearance of crisis communication and collective solidarity.